Linking the occurrence of marine yeasts with elemental concentrations in mussels from Saldana Bay and Langebaan Lagoon - Dames, Nicole Rebecca (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.